Fraud smart - Pickett, K. H. Spencer (Chichester,West Sussex,UK : John Wiley & Sons, 2012)
"A professional guide to developing training for fraud risk and detection. This book provides a simple but effective method of developing a fraud risk awareness strategy that focuses on training employees using a six-stage approach to this task that involves understanding the threat, appreciating respective responsibilities, embracing a sound moral compass, recognizing red flags, mastering suitable internal controls, and managing the risk of fraud. Using this step-by-step approach, all senior executives, managers, employees, and associates can develop an important new skill set that will help them understand and deal with the risk of fraud in the workplace"
1. Understanding the threat -- 2. Appreciating respective roles -- 3. Embracing sound ethics -- 4. Recognizing red flags -- 5. Mastering suitable controls
Includes index
Keywords: Auditing, Internal; Employee crimes -- Prevention; Employee theft; Fraud -- Prevention